Engaging health plans to prioritize HPV vaccination and initiate at age 9 - Shaylen Foley; Jennifer Nkonga; Marcie Fisher-Borne (Taylor & Francis Group, 2023)
Health plans can influence pediatric and primary care providers and patients to understand HPV vaccination coverage and increase HPV vaccination uptake. By initiating vaccination at age nine, health plans can lay the groundwork for on-time HPV cancer prevention by age 13. In 2022, the American Cancer Society engaged 28 health plans in a 12-month HPV vaccination learning collaborative in which plans set their own quality improvement targets, implemented multi-pronged interventions, and joined quarterly best-practice sharing calls. Twenty-five of the 28 plans reported including a focus on ages 9 to 10. Preliminary pre-intervention data illustrate that vaccination rates from participating plans follow national trends and reaffirm existing gaps for HPV vaccination. Health plan interventions to address HPV vaccination are consistent with best practices but could be maximized to target initiation at ages 9-10 by using provider and patient reminders, targeted provider education, and dose-specific provider pay for performance and patient incentive programs. Health plans should explore future capacity to analyze non-HEDIS required data, including HPV initiation and HPV vaccination data for adolescents below age 13.